TINJAUAN PENANGANAN PENYALAHGUNAAN IZIN TINGGAL KUNJUNGAN WARGA NEGARA ASING OLEH KANTOR IMIGRASI KELAS III NON TPP IMIGRASI BAUBAU TAHUN 2019 DALAM PERSPEKTIF KEAMANAN NASIONAL - Faturachman Alputra Sudirman; Opi Purnama Zatun Bay Hamzah (Universitas Halu Oleo, 2021)
This study aims to identify and explain the forms of abuse of visit residence permits committed by foreign nationals in the working area of the Class III Non-Immigration Checkpoints Baubau; as well as describing the handling of abuse of residence permits visiting foreign nationals by the Immigration Office Class III Non-Immigration Checkpoints Baubau. Using qualitative research methods with an analysis of the national security approach. The results of the study show that throughout 2019 there were three forms of abuse of visit residence permits in the work area of the Baubau Immigration Office, namely overstaying, working in Indonesian territory without using a work visa, and marrying Indonesian citizens outside the applicable regulations in Indonesia. In dealing with the abuse of stay permits for visiting foreign nationals, the Baubau Immigration Office provides administrative sanctions in the form of deportation from the Indonesian Territory under Law Number 6 of 2011 concerning Immigration Article 75 Paragraph (2) letter f.